Sources of economic growth in MENA countries: A Harrod-neutral technological progress identification framework - Acikgöz Senay; Mohamed Sami Ben Ali; Merter Mert (Kiel Institute for the World Economy (IfW), 2017)
This study answers the question: What are the results of assuming the nature of technological progress as Harrod-neutral in growth accounting for the Middle East and North African (MENA) countries? Accordingly, this study contributes to the debate over whether the sources of economic growth stem from technological progress, capital or human capital accumulation. The study finds evidence that economic growth stems from capital accumulation rather than total factor productivity for the MENA countries, except Israel and Saudi Arabia. The authors concluded that assuming the nature of technological progress as Harrod-neutral in growth accounting for the MENA countries does not have a critical impact on the results.
Keywords: O30; O47; O57; C22; 330; sources of economic growth; growth accounting; human capital; bounds testing; ARDL; MENA